2015
DOI: 10.1002/jmor.20491
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin administration induced reactivation in the seminal gland of the soay rams during non‐breeding season: An ultrastructural and morphometrical study

Abstract: Fifteen adult Soay rams were used in this experiment. Eight animals were given subcutaneous implants containing melatonin, while the other seven animals were used as control. After 11 weeks, the rams were killed and the seminal vesicles were examined by light and electron microscope. In contrast to the control grouped animals, the melatonin treated rams showed morphological, morphometrical, and ultrastructural changes as a result of reactivation of the glandular tissues of the seminal glands. The ratio of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In the seminal vesicles, IHC showed a nuclear location for the MT 1 melatonin receptor, while that for MT 2 was found in the cytoplasm. Very recent studies have demonstrated that melatonin treatment during the non-reproductive season reactivates the ram seminal vesicles [39] and increases their size in the Iberian ibex [40]. Therefore, it is likely that both effects may be exerted through the melatonin receptors we have here identified.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the seminal vesicles, IHC showed a nuclear location for the MT 1 melatonin receptor, while that for MT 2 was found in the cytoplasm. Very recent studies have demonstrated that melatonin treatment during the non-reproductive season reactivates the ram seminal vesicles [39] and increases their size in the Iberian ibex [40]. Therefore, it is likely that both effects may be exerted through the melatonin receptors we have here identified.…”
Section: Discussionmentioning
confidence: 76%
“…In fact, melatonin treatment reactivates the seminal vesicles during the non-reproductive season [39], increasing their size [40]. It also modulates the contraction of the vas deferens [41].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TCs have also been described in human skin [Rusu et al, 2011], skeletal muscle and lung [Popescu et al, 2011], as well as in the human and rat parotid gland [Nicolescu et al, 2012a]. Our previous study [Mokhtar et al, 2016] revealed their presence in seminal vesicles of the Soay ram for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Soay rams (breed Ovis aries ) were obtained from specialist breeders in Scotland [Mokhtar et al, 2016]. The animals were kept in outdoor grass paddocks at the Animal Breeding Research Organization's field station at Dryden, near Edinburgh, during long summer days with 16 h of light and 8 h of darkness, and were fed a standardized diet of grass pellets (500 g/animal; Vitagrass, Grange-over-Sands, UK) given daily.…”
Section: Animalsmentioning
confidence: 99%
“…Telocytes in the duodenum established a close contact with neuroendocrine cells as well as eosinophils, which might be involved in immune response [Cantarero Carmona et al, 2011]. Telocytes mediate activation of progenitor cells to repair different tissues and organs: heart, lung, skeletal muscle, skin, meninges, choroid plexus, eye, liver, uterus, urinary system [Bei et al, 2015], and ram seminal vesicles [Abd-Elhafeez et al, 2017;Mokhtar et al, 2016]. Telocytes may have a protective function against oxidative stress and cellular aging in the lung [Zheng et al, 2014].…”
Section: Introductionmentioning
confidence: 99%